PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO BUSANA HJ NENENG DI PANDEGLANG BANTEN - Fikri Yusup Mubarok; Triyadi Triyadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. The purpose of this study was to determine the Price Variable (X1), Product Quality (X2) and the Influence of Price and Product Quality on Purchasing Decisions at the Hj.Neneng Fashion Store in Pandeglang Banten. This research method uses a quantitative method with a quantitative descriptive approach. The sample used in this study used the entire population of 96 consumers as respondents. In this study, the sampling technique used was probability sampling. The results of the Price variable significantly influenced the Purchasing Decision with a t count of 7.335> t table of 1.661 and a Sig. value <0.05 (0.0000 <0.05). The results of the Product Quality variable significantly influenced the Purchasing Decision with a t count of 9.849> t table of 1.661 and a Sig. value <0.05 (0.000 <0.05). The results of the Price and Service Quality variables simultaneously have a significant effect on Purchasing Decisions with a calculated f value of 73.043 > 3.09 and a Sig. value < 0.05 (0.000 < 0.05). Keywords: Price, Product Quality, Purchasing Decisions